Optimalisasi Rute Distribusi pada Gudang YU Pet Shop Guna Meminimalkan Biaya Transportasi - Arif, Erwan; Purnama, Jaka (Fakultas Teknik UMRI, 2025)
YU Pet Shop warehouse faces inefficiencies in the distribution of cat food, as delivery routes are manually determined by drivers without considering distance or vehicle capacity. This study aims to optimize distribution routes using the Ant Colony Optimization (ACO) method to reduce operational costs, particularly fuel and labor expenses. The results show that the total monthly travel distance can be reduced from 852 km to 661.6 km, achieving an efficiency gain of 22.34%. This reduction leads to monthly fuel savings of IDR 144,160 and labor cost savings of IDR 400,000. Therefore, the implementation of ACO has proven effective in improving distribution efficiency and significantly reducing transportation costs, thus supporting a more competitive and efficient company operation.